P‐21: Three‐Mask Elevated‐Metal Metal‐Oxide Thin‐Film Transistor Technology for High‐Resolution AMOLED Application. Issue 1 (30th May 2018) - Li, Jiapeng; Lu, Lei; Xia, Zhihe; Wang, Sisi; Feng, Zhuoqun; Kwok, Hoi-Sing; Wong, Man
Abstract : Incorporated with the self‐aligned definition of the active island, a one‐mask‐reduced elevated‐metal metal‐oxide (EMMO) thin‐film transistor (TFT) with thermally‐induced source/drain regions was proposed for high‐resolution AMOLED application. Such three‐mask EMMO TFT combines the advantages of small device footprint, low manufacture cost, reduced overlap parasitic capacitance and good device characteristics.